Associação genética de características de qualidade de carne e precocidade sexual em animais Nelore (Bos indicus) - Andrade, Willian Bruno Fernandes de [UNESP] (2015)
Brazil has a world's prominent role in the agricultural sector, and the largest commercial herd in the world, occupying, nowadays, the position of largest beef exporter. The country's herd is mainly composed of Bos indicus breed, specially Nellore breed. However, it is known that, in general, Bos indicus breeds have low productivity index and produces meat of lower quality then Bos taurus. Seeking for alternatives that may improve the efficiency and productivity of the animals, increasing the profitability and the meat quality produced in the country, is the challenges of the Brazilian livestock. Therefore, assessing the genetic association between traits that have direct influence on the productivity may contribute to the improvement of the sector. Within this context, elucidating the genetic association between sexual precocity of females and fat deposition in Nellore, providing tools to identify animals (bulls) that produce calves that are early in carcass finishing and sexually precocious heifers, may contribute to short the production cycle of beef cattle and increase profitability and productivity of the system. Thus, the aim of the present study is to estimate the genetic correlations between sexual precocity trait and meat quality traits in Nelore cattle, in order to obtain informations that can be incorporated into animal breeding programs. For sexual precocity trait, all records of females that were born from 1993 to 2012 were used. For carcass and meat quality traits were used only males, born from 2008 to 2011, fed for finishing in a period of 90 days. Variance components were estimated by Bayesian inference using bull linear model for the EGS characteristics, MARM and LIP and non-linear sire model (threshold) to PREC. Two-trait analyzes were carried out, involving the PREC feature and one of the three characteristics, EGS, MARM or LIP. The heritability estimates obtained by bi-trait analyzes were 0.06, 0.03 and 0.05, for ...